Feminism in A Room with A View Novel: Critical Analysis - Rahma Yunita Putri; Anisha Bunga Armethia Fitriane; Rizki Aji Saputro; Aldy Maulitta (Jurnal Langua, 2022)
Feminist play with a range of choice in the process self-presentation, registering a relation both to the body and to the social meaning of womenhood. The main focus of this research is comparing and measuring the feminist issues by reading the novel "A Room with a View". The purpose of this study is describing feminist issues that happened in the novel. This type of research is qualitative descriptive, the writer uses observation documentation as the technique of gaining and measuring data with reading intensively. The sample data in this research was every scenes that the writer belief the dialogue was cosists with feminism act, read intensively in every scenes. Based on the observation, the writer find some topic and issues that happened in the novel "A Room with a View", the problem faced by the author is the language style that use in the novel, so the writer decide to read intensively to knowing the true meaning of each dialogues. This research concluded that there was a lot of feminism issues that happened in the novel "A Room with a View" even though there are still obstacles with problems to understand with the language style. Keywords: feminist, a room with a view, novel